2013
DOI: 10.1007/s10803-013-1993-6
|View full text |Cite
|
Sign up to set email alerts
|

Using the Circumplex Model of Affect to Study Valence and Arousal Ratings of Emotional Faces by Children and Adults with Autism Spectrum Disorders

Abstract: The Affective Circumplex Model holds that emotions can be described as linear combinations of two underlying, independent neurophysiological systems (arousal, valence). Given research suggesting individuals with autism spectrum disorders (ASD) have difficulty processing emotions, we used the circumplex model to compare how individuals with ASD and typically-developing (TD) individuals respond to facial emotions. Participants (51 ASD, 80 TD) rated facial expressions along arousal and valence dimensions; we fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Although there are numerous studies in which high functioning individuals with ASD have reported affective states using self-report instruments (e.g., Sasson et al, 2012; Tseng et al, 2014; White et al, 2014), another potential limitation of the present study is the long-standing issue of the validity of self-report of affective states in ASD (Berthoz & Hill, 2005; Kaat & Lecavalier, 2015), and future research that addresses the correspondence between self- and caregiver-report indices of positive affect in ASD will be needed to address this issue. We highlight in this regard, however, that the ASD and control groups in this study showed relatively equivalent levels of positive affect, suggesting that the ASD group understood the meaning of PANAS-C items (although this observation is clearly not sufficient to establish the validity of self-reported positive affect in the ASD group, which should be addressed in future studies).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous studies in which high functioning individuals with ASD have reported affective states using self-report instruments (e.g., Sasson et al, 2012; Tseng et al, 2014; White et al, 2014), another potential limitation of the present study is the long-standing issue of the validity of self-report of affective states in ASD (Berthoz & Hill, 2005; Kaat & Lecavalier, 2015), and future research that addresses the correspondence between self- and caregiver-report indices of positive affect in ASD will be needed to address this issue. We highlight in this regard, however, that the ASD and control groups in this study showed relatively equivalent levels of positive affect, suggesting that the ASD group understood the meaning of PANAS-C items (although this observation is clearly not sufficient to establish the validity of self-reported positive affect in the ASD group, which should be addressed in future studies).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variability in performance on face processing tasks in the ASD population. This variability is seen across age groups in fixation patterns [Amestoy, Guillaud, Bouvard, & Cazalets, ], ratings of the arousal and valence of emotional stimuli [Tseng et al, ], and identity and expression recognition [Greimel et al, ]. Thus, samples of children [Braverman, Fein, Lucci, & Waterhouse, ; Teunisse & de Gelder, ; Wilson, Brock, & Palermo, , ], adolescents [Rutherford, Clements, & Sekuler, ], and adults [Barton et al, ], all include some subgroups that show face and affect processing that is consonant with their mental age, and others that show atypical performance.…”
Section: Individual Difference Factors Contributing To Face Processinmentioning
confidence: 99%
“…The circumplex model of affect suggests that dysregulated arousal systems would have a direct impact on the experience of all emotions, and Tseng and colleagues (2013) recently found that a circumplex model of experienced affect is characteristic of individuals with ASD. One potential mechanistic account for impaired ER, and the resultant increased anxiety, in ASD is that individuals on the spectrum may experience heightened levels of basal or reactive arousal.…”
Section: Overview: Emotion Regulation and Anxiety In Asdmentioning
confidence: 99%